Sexual Abuse Disertai Kehamilan Tidak Direncanakan atau Dikehendaki pada Remaja dengan Intellectual Disability: Sebuah Laporan Kasus - I Made Darmayasa; Tri Oktin Windha Daniaty; AA Sri Wahyuni (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2022)
AbstractBackground: Intellectual Disability in adolescents is prone to physical, mental, and sexual violence. Intellectual and adaptive disabilities make adolescents with intellectual disabilities unable to avoid environmental behavior including sexual abuse. Methods: A case report of a 12-year-old teenager with an Intellectual Disability who became pregnant as a result of sexual abuse by an unknown person. On the way, she had an abortion. Results: On examination, it was found that a 12-year-old teenager with mild mental retardation, without education, came from an incomplete family with very poor socioeconomic status. The diagnosis was confirmed by a multiaxial approach and concluded that adolescents with mild mental retardation have significant behavioral impairment and require attention or therapy (F70.1). Patients are also submissive and quiet with ego defense mechanisms that regression, and have problems with mental and intellectual development. Multidisciplinary management was carried out involving the social and medical departments.Summary: Patients with Intellectual Disabilities, especially adolescents, require special attention and a multidisciplinary, and comprehensive approach, starting from prevention, as well as in carrying out treatment.